Urticaria, nephritis, and pseudotumor cerebri - Lieberman, Jefrey; Gepflardt, Gordon; Calabrese, Leonard H. (Cleveland Clinic Journal of Medicine, 1990)
The spectrum of chronic urticarial disease ranges from chronic urticarial skin lesions alone to well-characterized systemic lupus erythematosus with urticarial vasculitis as the major skin manifestation. Within this spectrum is the syndrome of urticarial vasculitis associated with systemic disease manifestations. There have been six previously recorded cases of urticarial vasculitis associated with pseudotumor cerebri. At least two of these have included membranoproliferative glomerulonephritis. The authors report a case of chronic urticarial disease associated with pseudotumor cerebri and membranoproliferative glomerulonephritis, but without demonstrable vasculitis. It is possible that this represents a distinct entity within the spectrum of chronic urticarial disease and can be easily screened for in clinical practice.